2000
DOI: 10.1128/jvi.74.3.1578-1586.2000
|View full text |Cite
|
Sign up to set email alerts
|

Papio cynocephalus Endogenous Retrovirus among Old World Monkeys: Evidence for Coevolution and Ancient Cross-Species Transmissions

Abstract: To study the evolutionary history of Papio cynocephalus endogenous retrovirus (PcEV), we analyzed the distribution and genetic characteristics of PcEV among 17 different species of primates. The viral pol-env and long terminal repeat and untranslated region (LTR-UTR) sequences could be recovered from all Old World species of the papionin tribe, which includes baboons, macaques, geladas, and mangabeys, but not from the New World monkeys and hominoids we tested. The Old World genera Cercopithecus and Miopithecus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
(13 reference statements)
0
17
0
1
Order By: Relevance
“…The calculation of synonymous amino acid change/nonsynonymous amino acid change ratio showed that primate TRIM5␣ has evolved under positive pressure (43,48). Since it has been reported that some types of endogenous retroviruses are detected in a lineage-specific manner (14,27,28,32,60,65), it has been suggested that primate TRIM5␣ may have evolved to control specific endogenous retroviruses. However, it seems more likely that exogenous viruses would provide a greater selective pressure than endogenous retroviruses would.…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of synonymous amino acid change/nonsynonymous amino acid change ratio showed that primate TRIM5␣ has evolved under positive pressure (43,48). Since it has been reported that some types of endogenous retroviruses are detected in a lineage-specific manner (14,27,28,32,60,65), it has been suggested that primate TRIM5␣ may have evolved to control specific endogenous retroviruses. However, it seems more likely that exogenous viruses would provide a greater selective pressure than endogenous retroviruses would.…”
Section: Discussionmentioning
confidence: 99%
“…Episodic waves of lethal retrovirus infections may have contributed to this evolutionary pattern. The timing of some ancient retroviral epidemics has been deduced from the presence of endogenous retroviruses in the germ lines of mammalian species (2,12,19,21,25,26,28,35,44,45,58,59,61). Notably, several endogenous retroviruses appeared in primate germ lines during the same time periods in which two of the expansions of v1 length in the catarrhine TRIM5␣ proteins seem to have occurred.…”
Section: Fig 2 Phylogeny Of Primate Trim5␣ Sequences (A)mentioning
confidence: 99%
“…2B). About 9 to 13 million years ago, the simian endogenous retrovirus (SERV) and Papio cynocephalus endogenous retrovirus were introduced into the genomes of cercopithecine monkeys (26,58,59). The TRIM5␣ B30.2 v1 expansion to 28 residues occurred during this same period (Fig.…”
Section: Fig 2 Phylogeny Of Primate Trim5␣ Sequences (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, la presencia de ERVs muy similares en especies muy alejadas permite identificar transmisiones horizontales entre grupos animales, que, aunque ocasionales, pueden ser importantes (un muy alto nivel de homología entre secuencias de especies muy alejadas evolutivamente se interpreta como transmisión horizontal). Varios ejemplos de transmisiones de RVs de este tipo entre especies se han detectado entre mamíferos placentarios, donde parecen ser relativamente frecuentes, incluyendo transmisiones entre el hombre y otros primates (Benveniste y Todaro, 1974;Li et al, 2001;Koralnik et al, 1994;Mang et al, 2000). Pero también se han postulado infecciones horizontales recientes entre especies pertenecientes a distintas clases de vertebrados (Martin et al, 1999), como el SNV aviar (spleen necrosis virus), que parece haberse transferido desde un equidna (Monotrema) para después sufrir una radiación adaptativa en algunas familias de aves; el otro caso es entre marsupiales y placentarios, concretamente un retrovirus endógeno de koala que se ha transferido al gibón como un RV exógeno altamente oncogénico e infectivo.…”
unclassified